HUBUNGAN KECEPATAN DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA KELAS VIII.4 SMP NEGERI 32 PEKANBARU - Tunggak, Rahmat; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: The purpose of this study was to determine whether there is a relationship between the speed and explosive power of leg muscles with the long jump squat force results in Class VIII.4 Students of SMP Negeri 32 Pekanbaru. This research was conducted in September 2019, at 10:00 WIB until completion. This research was conducted at the SMPN 32 Pekanbaru sports field. This type of research is correlation research. The population that will be used is Class VIII.4 Students of SMPN 32 Pekanbaru who take PJOK courses consisting of 33 students. The sampling technique was purposive sampling in which in this study the sample consisted of 16 sons. From the results of this study it can be concluded that there is a very strong relationship together between the Speed and Explosion Power of the Leg Muscles and the Squat Force Long Jump Results in Class VIII Students of SMP NEGERI 32 Pekanbaru, where Rtab at a significant level (0.05) = 0.514 means Rhitung (0.810)> rtab (0.514). Key Words: Leg Muscle Speed and Explosion Power, Jumper Style Long Jump Results